2015
DOI: 10.1093/molbev/msv203
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Identification ofCis-Regulatory Rewiring Events in Yeast

Abstract: A coregulated module of genes ("regulon") can have evolutionarily conserved expression patterns and yet have diverged upstream regulators across species. For instance, the ribosomal genes regulon is regulated by the transcription factor (TF) TBF1 in Candida albicans, while in Saccharomyces cerevisiae it is regulated by RAP1. Only a handful of such rewiring events have been established, and the prevalence or conditions conducive to such events are not well known. Here, we develop a novel probabilistic scoring m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 63 publications
2
13
0
Order By: Relevance
“…Although this basic idea is now generally accepted, the past two years have provided new examples and added important insights. Specifically, there is new evidence from bacteria [22], fungi [2331], worms [32,33] sea urchins [34,35], flies [3638], plants [39], and mammals [4045] that evolutionary rewiring—that is, genetic changes in the connections between a regulator and its targets genes—is frequent. Using a common methodology to evaluate transcription evolution across a variety of animal species, Carvunis et al [46] concluded that evolutionary rewiring occurred at roughly similar rates (using years of divergences from a common ancestor as the denominator) in insects, birds, and mammals.…”
Section: Evolutionary Rewiring Is Extensive In All Clades Examinedmentioning
confidence: 99%
“…Although this basic idea is now generally accepted, the past two years have provided new examples and added important insights. Specifically, there is new evidence from bacteria [22], fungi [2331], worms [32,33] sea urchins [34,35], flies [3638], plants [39], and mammals [4045] that evolutionary rewiring—that is, genetic changes in the connections between a regulator and its targets genes—is frequent. Using a common methodology to evaluate transcription evolution across a variety of animal species, Carvunis et al [46] concluded that evolutionary rewiring occurred at roughly similar rates (using years of divergences from a common ancestor as the denominator) in insects, birds, and mammals.…”
Section: Evolutionary Rewiring Is Extensive In All Clades Examinedmentioning
confidence: 99%
“…Thus far, we argued here that transcription rewiring is common, and, in this section, we review evidence (predominantly from full-genome experimental and computational studies) that gives a rough idea of the frequency. Based on several independent studies in ascomycetes, it is estimated that, on average, ∼15% of the connections between a transcription regulator and its target genes in S. cerevisiae will be preserved in C. albicans (for example, see Borneman et al 2007;Tuch et al 2008b;Habib et al 2012;Sarda and Hannenhalli 2015;Nocedal et al 2017). Of course, the exact number depends on the particular regulator examined (as well as the methodologies used), but this rough average is a reasonable starting place for appreciating the overall extent of transcriptional rewiring.…”
Section: How Extensive Is Transcriptional Rewiring?mentioning
confidence: 99%
“…Our approach differs from that of Sarda and Hannenhalli [9] in that we define our skewness for each transcription factor while they define a function that compares the skewness of two transcription factors. They require more computation than our approach since they must make a complex computation of rewiring scores for each pair of transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…Sarda and Hannenhalli [9] present a method for detecting rewiring, switching one transcription factor to another transcription factor in the same 23 yeast species we investigate.…”
Section: Introductionmentioning
confidence: 99%